TRANSCRIPTIONAL PROFILE OF CANCER-TESTICULAR ANTIGENS IN PATIENTS WITH BREAST CANCER - D. I. Vodolazhskiy (SPb RAACI, 2018)
To identify new effective targets for immunotherapy of breast cancer, based on cancer-testis antigens (CTA), the associations were studied between CTA gene expression, clinical and pathological characteristics of breast cancer. Therefore, the aim of the study was to perform screening of CTAs specific to breast tissue tumors (luminal types A and B) based on assessment of the transcriptional profile of cancer-testis genes in the patients of different ages. To evaluate these relations, paired surgical biopsies (normal and tumor) of breast tissue of 32 patients (64 samples) aged 38-86 years were used. Relative expression of 16 genetic loci (MAGEA1, MAGEA2, MAGEA3, MAGEA4, MAGEB1, MAGEB2, GAGE1, GAGE3, GAGE4, MAGEC1, BAGE, XAGE3, NY-ESO1, SSX2, SYCP1 and PRAME1) was determined by the RT-qPCR. It was found that the transcriptional profile of CTA differs in different age groups of patients (at the age of < 55 years, overexpression of MAGEA3 was noted; after 55 years, MAGEA1, MAGEB1, BAGE, NY-ESO1, GAGE1 and GAGE3 were more expressed). In the luminal type A cancer, overexpression of MAGEA1, MAGEA2, MAGEA4, MAGEB1, MAGEB2, GAGE3, GAGE4, MAGEC1 and PRAME1, whereas in B type cancer, the genes with increased expression were not detected. These differences should be considered when planning immunotherapy, can be used as biomarkers for both breast cancer as clinical entity, and, in particular, for its individual subtypes.